Kajian Sistem Penyimpan Ikan Sementara pada Tempat Pendaratan Ikan (TPI) - Muhammad Yusuf; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2013)
Fisheries as one of the pillars of the local economy in Aceh Province that had been optimally utilized. Catches especially during the harvest tends to be sold by the fishermen to other areas due to lack of knowledge of post-harvest handling. One of the post-harvest processing is the preservation of a cooling system is usually done with the use of cold storage box (cold box) at the Fish Landing Places (TPI). This study aims to get the length of storage time of fish that can maintain a temperature of 0°C to 5°C, by using the 3 kinds of cold storage box is made of wood material, fiber and styrofoam. From the results of testing two methods: the method of fish in the middle of the ice around it and the traditional methods used by the community found that containers with wood coated styrofoam insulation to maintain temperature of 2°C, while the isolation box storage timber, fiber and styrofoam fish temperature exceeds 2.5°C. Wooden storage box covered with styrofoam has the most room temperature lower than the usualbox used by the community. This box is the ideal storage box, the construction is very simple. The box is fully insulated by wood and styrofoam.